Caracterização de imagens em livros didáticos e suas contribuições para o processo de significação do conceito de equilíbrio químico - Kiill, Keila Bossolani (Universidade Federal de São Carlos, 2009)
This work studies images contained in Chemistry textbooks approved by the PNLEM/2007. The goals of this research were: a) to characterize these images, discriminating those that compose Chemical Equilibrium Chapters, according to the chemical knowledge dimensions (macroscopic, submicroscopic and symbolic); and b) to evaluate the contributions brought by these images to the significance trial of that content. The methodology for data collection was the double-blind one, in which each researcher, independently, proposes a classification, that is later validated by means of statistical instruments. It was elaborated a taxonomy for data collection, wherein the categories of analysis were discriminated. To analysis of the images, is necessary consider the interrelations between them, therefore, in a same visual representation, is possible have the knowledge represented in two more dimensions. The theoretical referential substantiates itself in the meaning learning, proposed by Ausubel and collaborators, and also in the signs conceptions developed by Pierce. The analysis results showed that, in the total, the best part of the images represents the chemical knowledge considering only the macroscopic aspect or not classified. For the chemical equilibrium chapter, in general, proposed representations for helping the understanding of that content are also of macroscopic nature or not classified. Regarding to the trial of significance of chemical equilibrium content, contributions of others contents such as chemical reaction, kinetic chemical and stoichiometry were also considered for images analysis. Thus, it was possible to conclude that representations found in textbooks are of macroscopic nature and typify chemical systems properties. Moreover, an expressive amount of images merely presents illustrative character and other few correlates dimensional aspects. Therefore, images contained in general textbooks poorly collaborate to the significance trial of chemical equilibrium content.
CHARACTERIZATION OF IMAGES IN TEXTBOOKS AND THEIRS CONTRIBUTIONS TO THE SIGNIFICANCE TRIAL OF CHEMICAL EQUILIBRIUM CONCEPT
Keywords: Química - ensino; Livros didáticos; Imagem; Equilíbrio químico; CIENCIAS EXATAS E DA TERRA::QUIMICA